Phospholipase D1 inhibition sensitizes glioblastoma to temozolomide and suppresses its tumorigenicity. Issue 3 (10th September 2020) - Kang, Dong Woo; Hwang, Won Chan; Noh, Yu Na; Park, Kang Seo; Min, Do Sik
Abstract: Resistance of glioblastoma to the chemotherapeutic compound temozolomide is associated with the presence of glioblastoma stem cells in glioblastoma and is a key obstacle for the poor prognosis of glioblastoma. Here, we show that phospholipase D1 is elevated in CD44 High glioblastoma stem cells and in glioblastoma, especially recurring glioblastoma. Phospholipase D1 elevation positively correlated with the level of CD44 and poor prognosis in glioblastoma patients. Temozolomide significantly upregulated the expression of phospholipase D1 in the low and moderate CD44 populations of glioblastoma stem cells, but not in the CD44 High population in which phospholipase D1 is highly expressed. Phospholipase D1 conferred resistance to temozolomide in CD44 High glioblastoma stem cells and increased their self‐renewal capacity and maintenance. Phospholipase D1 expression significantly correlated with levels of temozolomide resistance factors, which were suppressed by microRNA‐320a and ‐4496 induced by phospholipase D1 inhibition. Genetic and pharmacological targeting of phospholipase D1 attenuated glioblastoma stem cell‐derived intracranial tumors of glioblastoma using the microRNAs, and improved survival. Treatment solely with temozolomide produced no benefits on the glioblastoma, whereas in combination, phospholipase D1 inhibition sensitized glioblastoma stem cells to temozolomide and reduced glioblastoma tumorigenesis. Together, these findings indicate that phospholipase D1 inhibition might overcome resistance to temozolomide and represents a potential treatment strategy for glioblastoma. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.